A Systematic Analysis of Various Word Sense Disambiguation Approaches - Chandra Ganesh; Sanjay K. Dwivedi; Satya Bhushan Verma; Manish Dixit (Advances in Distributed Computing and Artificial Intelligence Journal)
The process of finding the correct sense of a word in context is known as word sense disambiguation (WSD). In the field of natural language processing, WSD has become a growing research area. Over the decades, so many researchers have proposed the many approaches to WSD. A development of this field has created the significant impact on several Web-based applications such as information retrieval and information extraction. This paper contains the description of various approaches such as knowledge-based, supervised, unsupervised and semi-supervised. This paper also describes the various applications of WSD, such as information retrieval, machine translation, speech recognition, computational advertising, text processing, classification of documents and biometrics.